2017
DOI: 10.3389/fgene.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of X-Chromosome Gene Expression in Bovine Blastocysts Derived by In vitro Fertilization and Somatic Cell Nuclear Transfer

Abstract: To better understand X-chromosome reactivation (XCR) during early development, we analyzed transcriptomic data obtained from bovine male and female blastocysts derived by in-vitro fertilization (IVF) or somatic-cell nuclear transfer (SCNT). We found that X-linked genes were upregulated by almost two-fold in female compared with male IVF blastocysts. The upregulation of X-linked genes in female IVFs indicated a transcriptional dimorphism between the sexes, because the mean autosomal gene expression levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…However, in bovine embryos, we found XIST accumulation did not lead to globally reduced expression of X-linked genes, similarly to what has been reported for human embryos [9]. In agreement with our findings, microarray and RNA-seq analyses in bovine blastocysts demonstrated enhanced expression of X-chromosome-linked genes in intact female compared with male blastocysts, which indicates that dosage compensation had not initiated at this stage [21,56]. Interestingly, we did observe a significant increase of intense H3K27me3 spots within nuclei from the morula to the blastocyst stage, indicating that this histone modification also did not lead to global downregulation of X-linked genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in bovine embryos, we found XIST accumulation did not lead to globally reduced expression of X-linked genes, similarly to what has been reported for human embryos [9]. In agreement with our findings, microarray and RNA-seq analyses in bovine blastocysts demonstrated enhanced expression of X-chromosome-linked genes in intact female compared with male blastocysts, which indicates that dosage compensation had not initiated at this stage [21,56]. Interestingly, we did observe a significant increase of intense H3K27me3 spots within nuclei from the morula to the blastocyst stage, indicating that this histone modification also did not lead to global downregulation of X-linked genes.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the XIST coating of the inactivated X chromosome, several X-linked genes escape silencing and are still expressed, as has been demonstrated in human and rabbit embryos [9]. In bovine blastocysts, X-linked genes were expressed at higher levels in females compared with males, suggesting that X-chromosome inactivation was not yet operational [21]. These data suggest that downregulation of X-linked genes after XCI initiation is not uniformly conserved among species.Here, we examined the timing of XCI, its initiation in different lineage segregation, and regulation of X-linked gene expression during bovine embryo development.…”
mentioning
confidence: 64%
“…The comparisons enabled us to separately examine the effects of various NT-involved factors such as the manipulation, partial removal of oocyte/zygote cytoplasm, and donor genome reprogramming (Figure 1A ). We analyzed previous Pip-seq data (Min et al, 2017 ) obtained from individual blastocysts after PCR-mediated amplification of embryonic transcripts by pico-profiling (Min et al, 2015 , 2016 ). Each blastocyst group comprised 12 blastocysts, with six males and six females (with the exception of five female shNTs).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 35 RNA-seq libraries (12 IVF, 12 scNT, and 11 shNT blastocysts) were constructed using TruSeq DNA Sample Preparation kit (Illumina) (Min et al, 2015 , 2017 ). Two hundred nano grams of pico-profiled amplicons were applied to the End-repair reactions by incubating with End Repair Mix (Illumina) at 30°C for 2 h. The reactions were purified with AMPure XP beads (Beckman).…”
Section: Methodsmentioning
confidence: 99%
“…In cattle, the presence of XIST transcripts has been reported as early as the 2-cell stage (Mendonca et al, 2019). Microarray and RNA-seq analyses of bovine blastocysts demonstrated higher expression of X-linked genes in female compared with male embryos, indicating that dosage compensation initiates later (Bermejo-Alvarez et al, 2010; Min et al, 2017). A recent report has indicated that XIST accumulation and XCI in bovine embryos starts at the morula stage.…”
Section: Discusionmentioning
confidence: 99%